WHATSAPP AS A LEARNING TOOL DURING COVID -19 PANDEMIC: ADVANTAGES AND DISADVANTAGES - Sirajul Munir; Rita Erlinda; Hendra Eka Putra; Hanif Afrinursalim (International Journal of Educational Best Practices, 2021)
This present study explores the advantages and disadvantages of WhatsApp (WA) as a learning tool during Covid-19 pandemic. WA is a messaging application that can be installed on smartphones and has many useful features. Researchers are interested in researching since many students and lecturers choose WA as an application for continuous learning while one knows that many applications are actually intended for learning. The design of this research was a mix method (quantitative and qualitative). This research involved 168 respondents as a sample. The instrument of this research was an open-ended questionnaire. To analyze the questionnaire, the researchers used the data analysis based on Miles, Huberman, & Saldana (2014). Three steps were applied: data condensation, data display, and drawing & verifying conclusion. The study concludes that most of the respondents believed that WA has more advantages than disadvantages. The advantages include it is effective and easy to use; the features are helpful, save internet quota, very light, easy to do communication, easy to observe the students. The disadvantages, however, is easy for the students to cheat, old chats are easily piled up by the new chats, the upload size is limited, and member capacity in the group is limited.